Non-Metastatic Breast Cancer : Clinical Presentation and Patterns of Surgical Treatment - Tlefih, Abdulhadi J. (AL-Kindy College Medical Journal, 2009)
Background : Breast cancer is the most common cancer of women. When breast cancer is detected and treated early, the chances for survival are better. Surgery is the most important treatment for non-metastatic breast cancer. Al-Kindy Col Med J 2008 Vol.5(1) 40 Original Article Objectives : The aim of this study is to review different clinical presentation and to evaluate types of surgical procedures and complications in treatment of nonmetastatic breast cancer. Method : During the period from Jun 1998 to May 2005, 93 patients with non-metastatic breast cancer were diagnosed and treated surgically in 2 hospitals in Baghdad ( Hammad Shihab military hospital and Al-Kindy teaching hospital). Results : Women constituted ( 98.93% ), while men constituted (1.07%), with male to female ratio of (0.01:1). The peak incidence of non-metastatic breast cancer (25.8%) was at age group 51-60 years, while (60.2 % ) of cases happened in women over 50 years of age. The right breast was the most common side affected, and the upper outer quadrant of the breast was the most common location affected by cancer. Painless lump (91.4%) was the most common symptom, and the hard lump was the most common sign (100%). The highest frequency of cases was diagnosed in stage II followed by stage III, and invasive ductal cancer was the most common histopathologic type. (87.1 %) of patients underwent modified radical mastectomy, while (12.9%) underwent breast-conservation surgery. Breast-conservation surgery carried higher incidence of recurrent disease than modified radical mastectomy (33.3% vs.13.6%). Conclusion : The majority of patients with non-metastatic breast cancer were over 50 years of age, and the preponderance were diagnosed in stage II. Modified radical mastectomy may be preferable method for treatment as it carries a lower rate of local or distant recurrence than conventional breast-conservation surgery procedures